Assessment of Some Habits and Practices related to Complete Denture Wearing – A Survey of Subjects Reporting to Watim Dental Hospital - Sadia Daaniyal, Zarah Afreen, Ammarah Afreen, Eruj Shuja, Gulmina Saeed Orakzai, Aamna Khalil, Sadia Daaniyal, Zarah Afreen, Ammarah Afreen, Eruj Shuja, Gulmina Saeed Orakzai, Aamna Khalil (Journal of Rawalpindi Medical College, 2021)
Objective: To assess some habits and practices related to denture wearing among subjects reporting to Watim Teaching Dental Hospital, Rawalpindi. Materials and Methods: This is a cross-sectional study conducted at Watim Dental College, Rawalpindi, from December 2018 to August 2019. Using a pre-structured questionnaire, data were collected from 155 subjects having used complete dentures for a minimum of 6-months. The questionnaire consisted of information including the type of dentures, duration and frequency of denture wearing, and denture cleaning habits. Data were analyzed using SPSS version 20. Results: Out of 155 participants, 80 (51.6%) were male and 75 (48.4%) were females. 89 (57.4%) patients use toothbrushes and soap for denture cleaning. 139 (89.7%) participants didn’t wear dentures while sleeping and soaked them in water. 98 (63.2%) respondents were not using antiseptic oral rinse and were casual in mouth-cleaning. Conclusion: From this study, it is concluded that 65 (41.9%) subjects were cleaning their dentures once a day. The study also reveals that 65 (41.9%) edentulous participants were not able to clean their oral cavity. Dentists should emphasize the importance of recall visits to evaluate the status of denture hygiene along with mucosal surface examination. Patient motivation to follow hygiene instructions and informing them about the harmful effects of overnight wearing of dentures should be part of delivering the prostheses to them.